Scottish crime survey, 2003 (Scottish Crime and Justice Survey, 2007)
The Scottish Crime and Justice Survey (SCJS) is a social survey which asks people about their experiences and perceptions of crime in Scotland. The survey is an important resource for both the government and public of Scotland. Respondents are selected at random from the Postal Address File and participation in the survey is entirely voluntary. The main aims of the SCJS are to: provide reliable statistics on people's experience of crime in Scotland, including services provided to victims of crime, assess the varying risk of crime for different groups of people in the population, examine trends in the level and nature of crime in Scotland over time, collect information about people's experiences of, and attitudes on a range of crime and justice related issues. An important role of the SCJS is to provide an alternative and complementary measure of crime to police recorded crime statistics. For further details of the scope and methodology of the SCJS, please see documentation. Information about the survey and links to publications may be found on the Scottish Government's Scottish Crime and Justice Survey webpages.